Diseño de un biodigestor para una finca del recinto San luís de las mercedes del cantón las naves de la provincia de bolívar - Monar Castillo, Ulises Riquelme (2010)
The thesis project is designed based on real data from the current situation of a village in the resort "San Luís de las Mercedes" Canton las Navas Province of Bolívar, whose main business of this town i sfarming, so there is major source of biomass waste that can be used to produce biogas an biofertilizer, this being a place conducive to the development environmental and organic waste.